Clinical Benefits and Safety of Gemtuzumab Ozogamicin in Treating Acute Myeloid Leukemia in Various Subgroups: An Updated Systematic Review, Meta-Analysis, and Network Meta-Analysis - Xu, Qingyu; He, Shujiao; Yu, Li (Frontiers in Immunology, 2021)
Background: Previous trials demonstrated evidence involving total effects of gemtuzumab ozogamicin (GO), an anti-CD33 humanized antibody, on treating acute myeloid leukemia (AML). In this updated systematic review, meta-analysis, and network meta-analysis (NMA), we aimed to comprehensively explore clinical benefits and safety of GO in various subtypes of AML. Methods: PubMed, Embase, Cochrane, and Chinese databases were filtered to search randomized controlled trials (RCT) and retrospective cohort studies which compared clinical efficiency and toxicity of GO with non-GO group in AML. Random-effects models were used to calculate pooled effect sizes and 95% confidence intervals (CI). Relative risk (RR) was used for estimating complete remission (CR), early death and toxicity. Hazard risk (HR) was accomplished to evaluate survival. Results: 15 RCT and 15 retrospective cohort studies were identified (GO: 4768; Control: 6466). GO tended to improve CR (RR 0.95, p = 0.084), followed by significantly improved survival (overall survival: HR 0.86, p = 0.003; event-free survival: HR 0.86, p = 0.015; relapse-free survival: HR 0.83, p = 0.001; cumulative incidence of relapse: HR 0.82, p < 0.001). GO benefits of CR and survival were evident in favorable- and intermediate-risk karyotypes (p ≤ 0.023). GO advantages were also associated with nucleophosmin 1 mutations (p ≤ 0.04), wild-type FMS-like tyrosine kinase 3 internal tandem duplication gene (p ≤ 0.03), age of < 70 years (p < 0.05), de novo AML (p ≤ 0.017) and CD33(+) (p ≤ 0.021). Both adding GO into induction therapy (p ≤ 0.011) and a lower (< 6 mg/m2) dose of GO (p ≤ 0.03) enhanced survival. Prognosis of combined regimens with GO were heterogeneous in both meta-analysis and NMA, with several binding strategies showing improved prognosis. Additionally, GO was related to increased risk of early death at a higher dose (≥ 6mg/m2) (RR 2.01, p = 0.005), hepatic-related adverse effects (RR 1.29, p = 0.02) and a tendency of higher risk for hepatic veno-occlusive disease or sinusoidal obstruction syndrome (RR 1.56, p = 0.072). Conclusions: These data indicated therapeutic benefits and safety of GO in AML, especially in some subtypes, for which, further head-to-head RCT are warranted.